Camera configuration for accurate craniofacial mapping using photomodeler scanner - Alias, Nor Azira (Faculty of Geoinformation Science and Engineering, Universiti Teknologi Malaysia, 2010)
PhotoModeler (Eos Systems, Inc. Canada) Scanner contains new capabilities in a module called Dense Surface Modeling (DSM). The DSM exploits photo pairs to generate massive number of 3D points, thus automatically creates a point cloud similar to the output from laser scanning technique. The DSM technology required at least two images (stereo pair) from digital cameras to generate the three-dimensional (3D) model. Camera setup is an important factor for capturing high-accuracy data because several pairs of synchronized digital cameras are needed to capture the images for craniofacial area of subject. Consequently, a research was carried out to determine an optimal camera configuration for capturing high-accuracy point cloud. The photogrammetric data captured was evaluated using the laser scanned data as the bench mark. This paper provides a detailed discussion of the designed camera configuration, the procedures to process stereo-pair images and the evaluation of the 3D model visualization reconstruction using photo-based scanned and laser scanned data.